Histological characterization of sugarcane shoots in vitro rooting in liquid culture medium - Lelurlys Nápoles Borrero; Mariela Cid Ruíz; Maritza Escalona Morgado; Pedro Marrero Sánchez; Nelly Vásquez Morera; Oscar Concepción Laffitte (Biotecnología Vegetal, 2017)
In the sugarcane (Saccharum spp.) propagation in temporary immersion there are individual shoots or groups of shoots that require their in vitro rooting before being transferred to natural conditions. The objective of the present work was to characterize the in vitro rooting of sugarcane shoots in liquid culture medium by histological analysis. Sugarcane shoots cv. 'Ragnar' were rooted by two methods: static liquid culture medium (MCLE) and Temporal Immersion Bioreactor (BIT). As initial explants, individual shoots or groups of shoots were used together to form a ‘macolla’. The shoots were then acclimatized. To characterize rooting histologically, samples were taken for each culture form and explant type at 0, 3, 6 and 9 days of culture. It was demonstrated that in vitro rooting of shoots group directly in BIT is effective. This prevents further manipulation of the explants and satisfactory survival results (90%) are achieved in acclimatization. In addition, it was verified that root formation in stems, regardless of the method of cultivation used (MCLE or BIT), both in individual shoots and in groups of shoots, occurs from the continuous growth of perivascular parenchyma cells during first 3 days of culture. The most internal shoot of group of shoots also present a high rhizogenic potential, with root primordia characterized by a high root apex distinction and the presence of calyptra, influenced by the mechanical obstruction exerted by leaf pods of the shoot itself and adjacent shoots.